Maskulinisasi Ikan Cupang (Betta Sp) Melalui Perendaman Larva dengan Estrak Pasak Bumi, Propolis Madu dan 17α-Metyltestosterone - Noor Syarifuddin Yusuf; Inga Torang; Nahwani Nahwani (Universitas Batangahari Jambi, 2023)
The purpose of this research is to know the effectiveness of the use of Pasak Earth Extract, Propolis Madu and 17-α Metyltestosteron on the sex ratio of Betta sp. This study was conducted using a complete randomized design (RAL) with 4 treatments and 3 replications. The treatment consists of a treatment with immersion Estrak methanol tongkat (EPB) with a concentration dose of 10 ml / liter, treatment B by soaking propolis Honey with a concentration dose of 60 ml / liter, treatment C with immersion 17α-methyltestosterone at a concentration dose of 500 mg / Liter (control +) Treatment D by immersion using water without hormone (control -) The results showed that betta fish treated with 17α-methyltestosterone (control +) showed male percentage of 89.26%, the treatment of Pasak Bumi Extract Amounted to 68.54%. Treatment of Honey Propolis equal to 53.63% and hormonal treatment of 43.13%. (Control -). Genetically in normal circumstances fish will produce offspring with sex ratio of male and female 50%: 50%. Sex ratio can be directed to the majority of males and females in the interests of the technique of sex change. The higher percentage of male fish is an indicator of the success of masculinization techniques in fish.